2020
DOI: 10.1371/journal.pone.0240421
|View full text |Cite
|
Sign up to set email alerts
|

Increased microbial loading in aerosols produced by non-contact air-puff tonometer and relative suggestions for the prevention of coronavirus disease 2019 (COVID-19)

Abstract: Objective To evaluate the microbial loading in aerosols produced after air-puff by non-contact tonometer (NCT) as well as the effect of alcohol disinfection on the inhibition of microbes and thus to provide suggestions for the prevention and control of COVID-19 in ophthalmic departments of hospitals or clinics during the great pandemics. Methods A cross-sectional study was carried out in this study. A NIDEK NCT was used for intraocular pressure (IOP) measurement for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Some authors suggest that environmental contamination with SARS-CoV-2 is high in hospital settings where patients with COVID-19 are hospitalized [ 11 , 12 , 17 , 18 ]. Contamination of surfaces by asymptomatic individuals has also been demonstrated [ 10 ]; however, it is not yet clear whether asymptomatic individuals as well as patients with COVID-19 can contaminate the environment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that environmental contamination with SARS-CoV-2 is high in hospital settings where patients with COVID-19 are hospitalized [ 11 , 12 , 17 , 18 ]. Contamination of surfaces by asymptomatic individuals has also been demonstrated [ 10 ]; however, it is not yet clear whether asymptomatic individuals as well as patients with COVID-19 can contaminate the environment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, contact of mucous membranes with a contaminated surface and/or with droplets can also lead to infection with SARS-CoV-2 [12]. There are many opportunities for environmental contamination (air and surfaces) with SARS-CoV-2 in hospital settings where COVID-19 patients may be present [4,7,8]. On the contrary, evidence regarding environmental spread of SARS-CoV-2 in the community is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…[6] demonstrated that, when personal protective equipment is not used, droplet and inhalation transmission routes predominate over the contact route, contributing 35%, 57%, and 8.2% of the probability of infection. Some authors report that environmental contamination by SARS-CoV-2 is high in hospital settings [4,5,7,8] but it is not yet well known whether asymptomatic individuals can spread the infection in the same way as patients with coronavirus disease 2019 . Surface contamination by asymptomatic individuals has been demonstrated [9], but data in non-healthcare settings are still minimal.…”
Section: Introductionmentioning
confidence: 99%
“…However, such air pulses may lead to the dehiscence of the tear film and further generation of tear droplets. [8][9][10] By high-speed photography, the ejection of tear droplets after the impingement of air-puff had been captured, especially with the addition of lubricant drops. 8,9 Despite that the scatter of tear may consequently contaminate the surface of equipment, such droplet dispersion may be minimized by disinfection or application of shields.…”
mentioning
confidence: 99%
“…15 As the aerosol dispersion has been considered a potential route of COVID-19 transmission, 15 both the patients and operators may suffer the risk of exposure during the IOP measurement. The air samples collected after air-puff had revealed increasing microbial colonies in culture, 10 adding the risk of disease transmission. In light of this, studies about aerosols generated by NCT are instructive to the protection of fundamental examination in ophthalmology clinics.…”
mentioning
confidence: 99%